Karakteristik Briket Arang Sekam Padi dengan Penambahan Arang Cangkang Biji Karet - Ishak Alhafis; Raswen Efendi; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this research was the to best quality briquettes from a combination of rubber seed coals and rice husk charcoal. The treatments used were the different composition of rice husk charcoal with rubber seed shell charcoal, K1 (90% rice husk charcoal:10% rubber seed shell charcoal), K2 (80% rice husk charcoal:20% rubber shell charcoal), K3 (70 % rice charcoal husk:30% rubber seed shell charcoal), K4 (60% rice husk charcoal:40% rubber seed shell charcoal), and K5 (50% rice husk charcoal:50% rubber seed shell charcoal).Data obtained were analyzed using analysis of variance and followed by Duncan’s Multiple Range Test at 5% level. The best treatment is charcoal charcoal briquettes K5(50% rice husk charcoal:50% rubber seed shell charcoal) has a water content of 3.1085%, ash content 17.0099%, density content 1.1842 g/cm3, crushing strength content 0.0127 kg/cm2, calorific value of 5403.1761 kal/g, level of volatile matter32.0165%, and bound carbon content of 47.8651%.Keywords:briquettes, charcoal rice husk, rubber seed shell charcoal